Changes in the antibiotic susceptibility of anaerobic bacteria from 2007–2009 to 2010–2012 based on the CLSI methodology. (December 2016) - Hastey, Christine J.; Boyd, Halsey; Schuetz, Audrey N.; Anderson, Karen; Citron, Diane M.; Dzink-Fox, Jody; Hackel, Meredith; Hecht, David W.; Jacobus, Nilda V.; Jenkins, Stephen G.; Karlsson, Maria; Knapp, Cynthia C.; et al.
Abstract: Antimicrobial susceptibility testing of anaerobic isolates was conducted at four independent sites from 2010 to 2012 and compared to results from three sites during the period of 2007–2009. This data comparison shows significant changes in antimicrobial resistance in some anaerobic groups. Therefore, we continue to recommend institutions regularly perform susceptibility testing when anaerobes are cultured from pertinent sites. Annual generation of an institutional-specific antibiogram is recommended for tracking of resistance trends over time. Highlights: Antibiogram comparison from independent sites over a 6 year period. Recommendations for annual antibiograms to be completed by hospitals. Trends in antimicrobial susceptibility analyzed for key anaerobes.